1995
DOI: 10.1002/gcc.2870120205
|View full text |Cite
|
Sign up to set email alerts
|

N‐ and KRAS mutations in primary testicular germ cell tumors: Incidence and possible biological implications

Abstract: Recently, conflicting results have been reported on the incidence of RAS mutations in primary testicular germ cell tumors of adults (TGCTs). In four studies a low incidence of mutations (less than 15%) in a variety of TGCTs or derived cell lines was found, whereas in two other studies a high incidence of N- or KRAS mutations (over 40%) was shown. A total of 62 testicular seminomas (SE) and 34 nonseminomatous TGCTs (NS) were studied thus far. The largest series consisted of 42 TGCTs, studied on paraffin embedde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 17 publications
2
27
1
1
Order By: Relevance
“…Because we found one TGCT without expression of this gene, SOX5 does not seem to be the gene of interest. Involvement of KRAS2 in the pathogenesis of TGCTs has been suggested and questioned by di erent investigators and its role is largely unclear so far (Dmitrovsky et al, 1990;Moul et al, 1992;Olie et al, 1995). Moreover, it has been reported that activation of KRAS2 is not su cient for malignant transformation (Kumar et al, 1990;Rodenhuis, 1992;McCormick, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Because we found one TGCT without expression of this gene, SOX5 does not seem to be the gene of interest. Involvement of KRAS2 in the pathogenesis of TGCTs has been suggested and questioned by di erent investigators and its role is largely unclear so far (Dmitrovsky et al, 1990;Moul et al, 1992;Olie et al, 1995). Moreover, it has been reported that activation of KRAS2 is not su cient for malignant transformation (Kumar et al, 1990;Rodenhuis, 1992;McCormick, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This supports a model in which overexpression of a gene or genes on 12p is related to the invasive growth of the tumor cells rather than initiation of tumorigenesis. Various attempts have been undertaken to identify the gene of interest, including KRAS2 (Mulder et al, 1989;Moul et al, 1992;Ridanpa¨a¨et al, 1993;Olie et al, 1995) and CCND2 (Sicinski et al, 1996;Houldsworth et al, 1997;Schmidt et al, 2001;Skotheim et al, 2002). However, formal proof that these genes are involved is missing so far.…”
Section: Introductionmentioning
confidence: 99%
“…A small percentage of TGCTs has RAS mutations, [35][36][37] of which the clinical relevance was not studied. We showed previously that seminomas with a mutated RAS gene have survival advantage in vitro and have reduced apoptosis in the primary tumor.…”
mentioning
confidence: 99%